Differences between boys and girls in applied variables to assess motor skills - Lovrić, Franjo; Đolo, Karla; Tapia-Serrano, Miguel Ángel; Jelaska, Igor; Barać, Ivan (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Physical fitness is the capacity to perform different activities involved in everyday life. Aim of Study. The main goal of this study was to investigate gender differences among second graders in the physical activity level, physical fitness and fundamental movement skills. Material and Methods. In doing so, a sample of 78 children (35 girls, 43 boys, overall mean 7.34 ± ± 0.53 years) was measured using NPAQ (Netherland Physical Activity Questionnaire), FMS-Polygon, BOT-2 (Bruininks– Oseretsky Test of Motor Proficiency), F3 test and BMI. Results. The between-subject t-test was applied to determine whether a significant difference exists between the genders. Differences were found between boys and girls in applied physical fitness tests in two tests: F3 (t = 3.05; p = 0.003) and FMS-Polygon (t = –2.7; p = 0.007), while no significant differences were observed for BOT-2, physical activity (KA), sedentary activity (SA) and BMI. Conclusions. The applied between-subject t-test showed significant differences between the genders. Such differences were found between boys and girls in applied physical fitness tests in two tests F3 (t = 3.05; p = 0.003) and FMS-Polygon (t = –2.7; p = 0.007), while no significant differences were observed for BOT-2, physical activity (KA), sedentary activity (SA) and BMI.
Keywords: children; physical activity; motor skills; sedentary; activity; fundamental movement skills